Aerosol‐Based Synthesis of Multi‐metal Electrocatalysts for Oxygen Evolution and Glycerol Oxidation. Issue 9 (5th May 2022) - Cechanaviciute, Ieva A.; Bobrowski, Tim; Jambrec, Daliborka; Krysiak, Olga A.; Brix, Ann Cathrin; Braun, Michael; Quast, Thomas; Wilde, Patrick; Morales, Dulce M.; Andronescu, Corina; Schuhmann, Wolfgang
Abstract: Discovery of new catalysts is crucial for future growth and development of environmentally friendly energy conversion processes e. g. the production of hydrogen by water electrolysis. We developed an aerosol‐based synthesis technique as a comparatively fast and facile method to prepare multi‐metal catalysts. 22 different quinary metal compositions were synthesized and investigated with respect to their activity for the oxygen evolution (OER) and the glycerol oxidation (GOR) reactions. The impact of the element composition and the homogeneous distribution of the elements in the particles on catalytic performance were evaluated. The highest activity for OER was found for Co20 Cu20 Ni20 Fe20 Zn20 . For GOR, Ag‐containing catalysts were the most active, however, in most cases Ag was locally enriched and not homogeneously mixed with the other metals in the particles. Ag‐based catalysts outperformed similar compositions containing one or more noble metals. The GOR selectivity of selected catalysts during long‐term electrolysis was also investigated and it was shown that varying the catalyst composition via aerosol‐based synthesis is a potential way to modulate the GOR selectivity. Abstract : Mix and match : An aerosol‐based synthesis technique was developed as a simple method for the production of multi‐metallic catalyst particles. 22 different quinary catalyst compositions were synthesized and investigated for the oxygen evolution reaction (OER) as it is the limiting step during water electrolysis and hydrogen production. As an alternative to OER, all catalysts were further investigated for the glycerol oxidation reaction (GOR).